PENGARUH MEDIA AUDIO VISUAL BERMUATAN EDUCATION FOR SUSTAINABLE DEVELOPMENT PADA MATERI PERUBAHAN IKLIM UNTUK KETERAMPILAN BERPIKIR SISTEM SISWA SMP - Sekar Khairina Kusumawardani, - (2022)
This study aims to analyze the effect of audio visual media with education for sustainable development content on climate change material for system thinking junior high school students. This study also analyzed students' responses to the use of audio-visual media in learning activities. The method that used is pre- experimental. This research was conducted on 18 students in a junior high school fifth grades from a private junior high school in the city of Bandung using a convenience sampling technique. Data was collected by using instruments test in the form of essay questions and non-test in the form of student response questionnaires as a source of supporting data. Data processing techniques and analysis using the Wilcoxon test and N-Gain calculations. Based on the research instrument, it was found that the Wilcoxon test obtained a significance value of less than 0.05. It can be concluded that there is a significant difference between the pre¬test and post-test. However, after being analyzed using N-Gain , although there are significant differences, this learning media does not have a significant effect on students' systems thinking skills. This can be seen from the results of calculating the student 's N-Gain value of 0.2 which is included in the low category. Furthermore, the results of research on the student response questionnaire also showed that the student responses answered in agreement regarding the audio¬visual media containing education for sustainable development which had been used in accordance with the conditions or wishes and expectations of students. This study shows that audio-visual media containing education for sustainable development has no effect on students' systems thinking skills.